The Effect of Deep Breathing Relaxation Techniques on Intensity Mother's Pain in Labor the Initial Phase of Contractions in Midwifery Practice - Hanifah, Astin Nur; Sapitri, Ana; Karnely, Karnely; Fitri, Lidia; Sari, Wulan Citra; Treasa, Adisty Dwi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Deep breathing relaxation therapy is a breathing in the abdomen with a slow frequency and slowly, rhythmically, and comfortably by closing the eyes while breathing. The purpose of this study was to determine the effect of deep breathing relaxation techniques on the intensity of pain in mothers in labor at the Midwife Practice. Pre-experimental design method. The population in this study were mothers giving birth at the Midwife Practice. Purposive sampling technique. The analysis used was univariate and bivariate analysis using the Wilcoxon test. The results of the study showed that before the deep breathing relaxation technique was carried out, there were 73.3% who had moderate pain and 26.7% who had severe pain and after the deep breathing relaxation technique was carried out, there was mild pain 80%. % and moderate pain 20%. The results showed that there was an influence of deep breathing relaxation techniques on the intensity of pain in mothers giving birth, which was seen from the results of the post-test, the level of labor pain decreased. The conclusion of the study was that there was an influence of deep breathing relaxation techniques on the intensity of pain in mothers giving birth at the Midwife Practice. It is expected that midwives will play an active role in providing the use of deep breathing relaxation methods during labor to reduce the level of labor pain so as to improve services for patients.